Observational and causal analysis of the extreme freezing in Hubei Province in early February 2024 - Xuan CHEN; Min ZHONG; Sainan CHEN; Yu LUO; Sizhang XIONG; Yi LU; Ruixue LIU (暴雨灾害)
An extreme freezing weather occurred in Hubei during the early of February in 2024, which accompanying freezing rain, ice pellets, and snow occurred and the intensity of freezing rain ranks first since 1981. Based on conventional meteorological observations, dual-polarization radar, and reanalysis data, the characteristics of observation and the cause of extreme freezing rain process are analyzed to provide reference for accurate forecasting and refined warning services of complex freezing weather processes. The results are as follow. (1) This process occurred under the combined influence of the subtropical trough and the subtropical high, with the long-term convergence of the cold air from the east route, forming a typical circulation pattern where the southwest warm and moist air flows are superimposed on the low-level cold air, and a "cold-warm-cold" temperature sandwich structure conducive to the occurrence of freezing rain is formed in the vertical direction. The abnormally strong water vapor flux at 700 hPa, the abnormally high temperature at 700-800 hPa, and the abnormally low temperature at 925 hPa are the main reasons for the extreme intensity of the freezing rain. (2) The analysis of the relationship between precipitation phase and vertical temperature and humidity layer structure indicates that the cloud top height, the melting layer, and the thickness and strength of the low-level cold pad are the key factors determining the precipitation phase. In this process in Hubei Province, both freezing rain and ice pellets are melting mechanism precipitation, with ice pellets having a higher cloud top height, weaker melting layer thickness and strength, and stronger low-level cold pad thickness and strength than freezing rain. (3) The dual-polarization radar characteristics of this extreme freezing rain are manifested as strong echoes mainly concentrated near the 2~3 km height of the melting layer, with a clear 0 ℃ layer bright band feature, and echo intensity of 30~45 dBZ, the strongest reaching 50 dBZ, in and below the melting layer, the correlation coefficient remains at 0.7~0.95, with a clear gradient high value area, the differential reflectivity is positive, with a strength of 1~3 dB, up to 4 dB at most, which is not significantly different from rainfall, but differs significantly from the negative value of pure snow.